The Impact of WhatsApp on Students' Communication Patterns Toward Lecturers - Baiq Nisrina Nur Ubudiyah; Andi Anto Patak; Lely Novia (International Journal of Business English and Communication, 2023)
Communication is a process of exchanging information, ideas, opinions, ideas and thoughts of a person carried out by two or more people. The purpose of this paper is to find out the impact of WhatsApp on communication patterns between students and lecturers and the challenges of communicating using WhatsApp. In this study using qualitative methods with a narrative inquiry approach and for data analysis using thematic techniques. The informants in this study were 10 students of Business English Communication. The results obtained from this study show the positive and negative impacts of each communication pattern.